И.ЮСУПОВ ШЫҒАРМАЛАРЫНЫҢ ПОЭТИКАЛЫҚ ТИЛИ - Өтепбергенова, Г. (ILIM hám JÁMIYET, 2021)
The article discusses the features and theoretical foundations of literary language. Features of the use of artistic means and artistic and aesthetic functions in the works of the poet I. Yusupov are discussed.